Problematic binge-watching and its impact on mental health status among students in Puducherry: a cross-sectional study - Rajasekaran, Madhumitha; Venkatesan, Balaji; Senthil, Rajini; Santhaseelan, Amarnath (International Journal Of Community Medicine And Public Health, 2026)
Background: Binge-watching, or watching numerous episodes of a TV show back-to-back in one sitting, has been very popular in the last few years, especially among young people and students. Although it can be leisure, compulsive binge-watching can affect mental health. Objectives were to evaluate the prevalence of problematic binge-watching among college students in Puducherry and its association with students’ mental health status, which includes anxiety, depression, and stress levels. Methods: A Cross-sectional study among 360 students with 18-25 years in Puducherry was conducted using simple random sampling for a period of three months. Data were collected using a structured questionnaire that included sociodemographic details, questions related to binge-watching behavior, and three mental health scales patient health questionnaire-9 (PHQ-9), generalized anxiety disorder-7 (GAD-7) and perceived stress scale (PSS-10). The chi-square test was used for determining independence. A p<0.05 was considered statistically significant. Results: Out of 360, 53.3% were aged 18-20 years, and 51.6% were female. The majority belonged to urban (85.8%), and 56.1% were from the lower socioeconomic class. 63.6% of students binge-watched, predominantly on smartphones (71.6%). Even though age, gender, and socioeconomic status had no significant relationship with binge-watching, urban participants had a high association (p<0.001). Consistent associations were found between binge-watching and anxiety (p<0.001) and depression (p=0.008), but stress was not significantly related (p=0.764). Conclusions: This research highlights the psychosocial dangers of overusing screen-based entertainment in young adults, emphasizing the need for targeted counseling and awareness programs to encourage good watching habits and maintain student mental health.